Financial reporting by Malaysian local authorities : a study of the needs and requirements of the users of local authority finanacial accounts - Tayib, Mahamad (MCB University Press, 1999)
This study investigates and explores the needs and demands of Malaysian local authority taxpayers for financial information published by Malaysian local authorities. The study found, in the absence of standard financial reporting requirements placed on these authorities, a large expectation gap between the needs and demands of local taxpayers and the financial reporting practices adopted by Malaysian local authorities. Based on a sample of 305 local taxpayers in three local authorities studied, the results reveal that a significant percentage of taxpayers who expressed interest in reading the annual financial accounts of these authorities had a general desire for more financial information. The results also reveal that there are statistically significant differences in terms of taxpayers' willingness to pay local tax demands between local authorities with high local tax arrears and local authorities with medium and low local tax arrears if such financial information were to be provided.